(untitled) (African Journal of Biomedical Research, 2021)
Klebsiella pneumoniae strains are a major source of horizontal spread of antimicrobial resistance (AMR) using a plasmid coded AmpC β-lactamase (DHA-1). DHA-1-producing K. pneumoniae were reported in cases of bacteremia from many centers but yet to be reported from our center. We explored the antimicrobial susceptibility profile, significant virulence factors and phenotypic detection of DHA-1-producing strains among Klebsiella pneumoniae from Ibadan. Fifty-one non-repetitive isolates identified as Klebsiella pneumonia by Vitek 2 were analysed for antimicrobial susceptibility by disc diffusion on Mueller Hinton agar. The inducibility of the β-lactamases was detected by the blunting of the oxyimino β-lactam zone of inhibition surrounding cefoxitin disc. Klebsiella pneumonia ATCC 700603 control strain was included. Twenty-nine (56.9%) was confirmed as ESBL, while 98% (50/51) were resistant to the β-lactam inhibitor (Clavulanic acid), with 88% (44/50) showing high-level resistance while 31% (16/51) showed high-level resistance to Cefoxitin. Multiple Antibiotic Resistance index ranged from 0.18 – 1.00, with 21 (41.2%) being extensive drug resistant (XDR) and 11 (21.6%) are pan-drug resistant (PDR). Twenty (39.2%) and 16 (31.4%) were associated with bacteremia and UTI respectively. All were resistant to killing by human serum and 15.7% (8/51) were hypermucoviscous. Ten (19.6%) and 5.9% (3/51) from blood and urine respectively produced biofilm. Two (3.9%) demonstrated inducible AmpC β-lactamase. The observed antibiotic susceptibility profiles and presence of isolates with DHA-1, poses a threat to successful antibiotic treatments of infections, with transfer of inducible beta-lactam resistance among strains of K. pneumoniae and possible dissemination within the hospital and its environment. RUNNING TITLE: Inducible AmpC Beta lactamase and antibiotic resistance among Klebsiella pneumoniae KEY WORDS: Klebsiella pneumonia, DHA-1, Multidrug resistance, hypervirulent KP, Biofilm